2015
DOI: 10.1002/14651858.cd012013
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for self-harm in children and adolescents

Abstract: There are relatively few trials of interventions for children and adolescents who have engaged in SH, and only single trials contributed to all but two comparisons in this review. The quality of evidence according to GRADE criteria was mostly very low. There is little support for the effectiveness of group-based psychotherapy for adolescents with multiple episodes of SH based on the results of three trials, the evidence from which was of very low quality according to GRADE criteria. Results for therapeutic ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(144 citation statements)
references
References 169 publications
2
135
2
5
Order By: Relevance
“…Four SRs met the criteria for this review 23 24 33 34. In many cases, these SRs included the same trials, however, owing to differences in the inclusion criteria, methods of analysis and the databases searched, it was decided that all four SRs were worthy of inclusion and exploration within this review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four SRs met the criteria for this review 23 24 33 34. In many cases, these SRs included the same trials, however, owing to differences in the inclusion criteria, methods of analysis and the databases searched, it was decided that all four SRs were worthy of inclusion and exploration within this review.…”
Section: Resultsmentioning
confidence: 99%
“…Two SRs focused on young people who had presented to clinical services as a result of SH17 or SRBs including passive SI,23 and another SR focused on web-based and mobile psychosocial suicide interventions for young people. Three of the reviews included trials with young people aged between 12 and 25 years23 33 34 and one included trials with participants up to the age of 18 years 24. See table 1 for the characteristics of trials included in this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their third Cochrane review Hawton et al 15 identified only 11 trials of interventions for SH in children and adolescents. This was a surprisingly low number of trials, given that under 18s are a key target age group for SH interventions and suicidality is a relevant clinical issue in child and adolescent psychiatry 31 32.…”
Section: Treatments For Children and Young Peoplementioning
confidence: 99%